ANATOMI DAN IDENTIFIKASI EMPAT BELAS JENIS KAYU DARI MALUKU - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
General and anatomical features of fourteen wood species from Maluku were observed and described for identification purposes. Except for Heritiera littoralis Dryand and Tarrietia riedeliana Oliv., all wood species could be distinguished one from the others based on anatomical characters. A tentative identification key is presented.